The “Death” Card from the Tarot Pack Pierpont Morgan — Bergamo and Macabre Themes in Italian Art of the 14th and 15th centuries - Belova, Olga D. (Actual Problems of Theory and History of Art, 2025)
The Death image on the card from the tarot pack Pierpont Morgan — Bergamo doesn’t match with any of known iconographies of Death, which were widespread in the 15th c. The author supposes that “Triumph of Death” iconography is the nearest one to this tarot card, but does not deny the connection with some other iconographies of Death.
Keywords: Tarot; Death card; Triumph of Death; Pierpont Morgan—Bergamo pack; Dance of Death